HUBUNGAN ANTARA JENIS VAKSIN COVID-19 DENGAN EFEK SAMPING YANG DITIMBULKAN PADA MASYARAKAT DI KOTA BEKASI TAHUN 2022 - Alifia Maharani Setyoputri (2022)
On December 2019, there was an outbreak of the Coronavirus Disease (COVID-19). The beginning of the emergence of this virus in China, Wuhan and has attracted global attention. Many experts agree and believe that the best way to control the COVID-19 pandemic in a sustainable manner is to provide a COVID-19 vaccine. Each type of COVID-19 vaccine has different side effects and effectiveness. This study aims to determine the relationship between the type of COVID-19 vaccine and the side effects after the COVID-19 vaccination. This study is a quantitative study with a cross-sectional design in Bekasi City April-June 2022. The population in this study were all people in Bekasi City who had received the first dose of COVID-19 vaccination of 1,885,014 people. The sample of this study is 428 respondents using purposive sampling technique. Data collection using online questionnaires. The results showed that there were a significant relationship between the type of viral vector vaccine (POR: 26.6; 95% CI: 11.044-64.304), the type of mRNA vaccine (POR: 1 ,8; 95% CI: 1.178-3.044), history of COVID-19 infection (POR: 2.2; 95% CI: 1.119-4.353), and sex (POR: 1.6; 95% CI: 1.025-2.501) with side effects of COVID-19 vaccination. The conclusions obtained from this study are that there is a significant relationship between the type of vaccine and side effects after controlling for the gender variable and a history of COVID-19 infection. If you want a vaccine with minimal side effects, you can choose an inactive virus vaccine as long as it is available.